Management of Scoliosis in Children with Osteogenesis Imperfecta. Issue 7 (July 2017) - O'Donnell, Courtney; Bloch, Nikki; Michael, Nicole; Erickson, Mark; Garg, Sumeet
Abstract : Spinal deformities frequently develop in patients with osteogenesis imperfecta. Scoliosis is more prevalent and complex in more severely affected patients with osteogenesis imperfecta. Nonoperative management of spinal deformity in osteogenesis imperfecta with bracing is not effective in preventing curve progression. Bisphosphonates have shown a positive effect on bone density but do not prevent progression of deformity. Operative management is challenging and can range from noninstrumented fusion to segmental pedicle screw fixation with cement augmentation. Recent studies have shown safe and effective use of modern instrumentation for treatment of osteogenesis imperfecta scoliosis and advocate for cement augmentation to decrease instrumentation failure.